Input-output structure, international trade and economic development - Ortiz, Carlos Humberto (CIDSE, Centro de Investigaciones y Documentación Socioeconomica, 2021)
In his paper on the “Structure of Development”, Leontief (1963) claimed that underdeveloped countries are poorer because they are by far less economically diversified. In this paper it is shown that a model of international trade with strong international restrictions on factor mobility, a stable input-output structure, and a productivity externality due to input diversification, is consistent with Leontief ́s hypothesis. The model also implies a growth-rate gap between industrialized and less industrialized economies.